Will the Revolution Be Tweeted? Mapping Complex Data Patterns from Sites of Protest - Losh, Elizabeth; Coleman, Beth; Um Amel, VJ (AoIR Selected Papers of Internet Research, 2013)
Can Twitter really bring a dictator to his knees? Does Youtube stream information that is more influential than traditional news providers, such as New York Times? In the mainstream media debate between Clay Shirky and Malcolm Gladwell about whether or not “the revolution will be tweeted” both pundits make confidently totalizing arguments. In contrast, this panel looks at the radical rhetorics of activism alongside digital practices of the everyday by mapping specific data patterns and discursive conventions across time and space in networked media technologies.Speaking from theoretical perspectives of the international Feminist Technology Network, these papers use textual explication, concept mapping, and media visualization to expose the rich polyvocalism of heterogeneous Internet discourses, full of affect and agency, even if the imagined community to which these utterances appeal is not necessarily realized in embodied interactions of protest at the town hall, city square, or national capital. The flux of configurations of collective and personal expression that constitutes online political speech in North Africa, the Middle East, and India is also often difficult to reduce to linear and predictive trends, and even earlier models of “smart mobs” (Rheingold) and “tactical media” (Lovink) do not always neatly map on to user behaviors in situations of political crisis.It may be difficult to make direct correlations between the rise of revolutionary movements made manifest through large-scale street actions and the adoption of new distributed communication practices around information technologies, but researchers can examine how speech acts of protest can be conceptualized, facilitated, staged, ignored, negated, or thwarted in a culture of accelerated mediation and acknowledge the potential fragmentation of publics, the seeming disappearance of the civic, and, possibly, the dissolution of the nation state in the shift of globalization.The three speakers examine how digital status update services, such as Twitter, not only disseminate links, images, and video that spur political protest but also allow for new forms of political discourse around key terms that function as metadata.Speaker one describes the use of proper names in Twitter hashtags that reference key actors, concepts, and slogans in recent protests against sexual violence in India. Although American NGOs involved in the global women’s empowerment movement may want to see legal, medical, and social privacy practices that mirror those in political institutions in the West, the problem of rape may actually be more forcefully addressed if the victim is given a proper name that can function as a keyword for shared online discourse. Even if it is only a pseudonym, such as Damini or Amanat, as in the recent Delhi gang rape case, naming the victim serves a key informational purpose.Speaker two examines how recent theories of copresence and of networked publics help understand the integration of “human narratives” and “data narratives” that unfold turning times of accelerated political change. This speaker examines how it was not merely the dissemination of graphic images of a self-immolated protester that spurred the overthrow an oppressive Tunisian regime, but the way that the violence against the body of Mohamed Bouazizi was understood through a hashtag with his name. Using the framework of object studies, this speaker will examine how the “body at risk” can be mapped across networked publics.